Peran Media Sosial Instagram Dalam Membangun Citra Dan Elektabilitas Calon Wali Kota Kota Bekasi Pada Pilkada 2024 - Michelle Putri Pardede; Iswadi Iswadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of ICT has driven changes in political campaign strategies, where Instagram is used by Bekasi Mayoral candidates to build their image, convey programs, and get closer to voters. This platform is effective in shaping public perception visually and emotionally. This study aims to examine the role of Instagram in influencing the image and electability of candidates in the 2024 Pilkada in Bekasi City. This study adopts a qualitative approach as the main method in the process of data collection and analysis. The results of the study show that Instagram has become an effective political communication medium for Bekasi Mayoral candidates in the 2024 Pilkada, by utilizing features such as feeds, reels, stories, and live to convey programs, build interactions, and strengthen political images. An attractive visual approach, relevant local narratives, and relaxed but polite language have proven to be able to attract attention, especially young voters. Two-way interactions that are actively carried out through social media increase emotional involvement and public trust, which has a direct impact on increasing electability. However, the use of Instagram also presents ethical challenges, such as the risk of content manipulation and the spread of disinformation, so digital campaign strategies must be managed honestly, openly, and ethically in order to effectively build public trust and support.